Methodological Rigor in the Curricular Evaluation - Andrea Ramírez-González (Universidad Nacional, Costa Rica, 2011)
This essay develops the importance of the methodological rigor in a curricular evaluation. The assessment of the curricular evaluation by the interested parties has to show the assessor's rigor with which the process has been realized, in this way it is possible to demonstrate elements that make the evaluation valid, reliable and creditable. The rigor of the evaluation is sustained with the articulation of aspects that are significant, assessable, theoretical, and methodological, of participation of the actors and of ethics which allow delimiting and developing the object to be evaluated. Therefore, each of these aspects is an essential part of the way to continue in an evaluative process.